2000
DOI: 10.1128/mcb.20.11.3880-3886.2000
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Signals Regulate GALTranscription in Yeast

Abstract: Gal4p activates transcription of the Saccharomyces GAL genes in response to galactose and is phosphorylated during interaction with the RNA polymerase II (Pol II) holoenzyme. One phosphorylation at S699 is necessary for full GAL induction and is mediated by Srb10p/CDK8 of the RNA Pol II holoenzyme mediator subcomplex. Gal4p S699 phosphorylation is necessary for sensitive response to inducer, and its requirement for GAL induction can be abrogated by high concentrations of galactose in strains expressing wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 69 publications
7
80
0
Order By: Relevance
“…The Gal4 activation domain has previously been shown to interact with TBP, TFIIB, and Srb4 (Melcher and Johnston 1995;Wu et al 1996;Ansari et al 1998;Koh et al 1998). In addition, Gal4 becomes phosphorylated upon induction and this phosphorylation is important for Gal4 activation (Rohde et al 2000). Therefore, it seems clear that SAGA is not the only factor important in activation, and multiple interactions are probably required for the normal establishment and maintenance of the activated state.…”
Section: Discussionmentioning
confidence: 99%
“…The Gal4 activation domain has previously been shown to interact with TBP, TFIIB, and Srb4 (Melcher and Johnston 1995;Wu et al 1996;Ansari et al 1998;Koh et al 1998). In addition, Gal4 becomes phosphorylated upon induction and this phosphorylation is important for Gal4 activation (Rohde et al 2000). Therefore, it seems clear that SAGA is not the only factor important in activation, and multiple interactions are probably required for the normal establishment and maintenance of the activated state.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation at only a single serine residue (Ser699) in the C-terminal activation domain appears to be necessary for activation (228). However, phosphorylation of Ser699 is not absolutely required for Gal4p activity, since a Ser699-Ala Gal4p mutant shows transcriptional activity in cells lacking Gal80p or in the presence of high galactose levels (219). From these observations, Rohde et al (219) suggested a model in which phosphorylation of Gal4p is required for an acute response to galactose.…”
Section: Activation By Phosphorylationmentioning
confidence: 99%
“…TTE1929, TTE1928 and TTE1927 are annotated as GalT, GalK and GalE, respectively, TTE1926 as GalR of the ROK (repressor, open reading frame and kinase) family (Titgemeyer et al, 1994), and TTE1925 as a hypothetical protein. On the other hand, the regulator of this putative operon, GalR, is predicted to be not, as usual, divergently transcribed (Ajdic & Ferretti, 1998;Mackie & Wilson, 1972;Rohde et al, 2000), but in the same direction as the other four genes. Since this was the first investigation of the gal operon in clostridia, it was desirable that the theoretical model could be supported by experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Several different uptake systems transport galactose into the cytoplasm, while a unique pathway, the Leloir pathway (Frey, 1996), subsequently converts the galactose to glucose 1-phosphate. The Leloir pathway is known to be composed of gene products from either the lac-gal regulon (Vaillancourt et al, 2002;Vaughan et al, 2001) or the gal operon (Ajdic & Ferretti, 1998;Bettenbrock & Alpert, 1998;Mackie & Wilson, 1972;Rohde et al, 2000;Weickert & Adhya, 1993). The lac-gal regulon consists of the genes involved in lactose and galactose metabolism, such as galRKTEM-lacSZ in Streptococcus thermophilus (Vaughan et al, 2001), while the gal operon contains the genes that participate in galactose metabolism, such as galETKM in Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%